2018
DOI: 10.1001/jamaoncol.2018.0137
|View full text |Cite
|
Sign up to set email alerts
|

Association of Muscle and Adiposity Measured by Computed Tomography With Survival in Patients With Nonmetastatic Breast Cancer

Abstract: Sarcopenia is underrecognized in nonmetastatic breast cancer and occurs in over one-third of newly diagnosed patients. Measures of both sarcopenia and adiposity from clinically acquired CT scans in nonmetastatic patients provide significant prognostic information that outperform BMI and will help to guide interventions to optimize survival outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
370
2
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 382 publications
(409 citation statements)
references
References 20 publications
13
370
2
3
Order By: Relevance
“…Several studies have demonstrated the influence of low muscle mass (sarcopenia) and/or poor muscle quality (low radiodensity) on cancer prognosis, reporting prognostic cut‐off values based on the statistical method of optimal stratification for respective parameters. Optimizing a cut‐value by minimizing the P ‐value, however, can lead to bias, namely, an overestimation of the prognostic impact as the cut‐offs so determined heavily dependent on the case mix in the respective study populations, for example, according to age, gender, ethnicity, cancer type, and stage, and consequently cannot be applied uniformly in different cohorts as exemplified by considerable different cut‐off values reported in an Asian cohort compared with North American cohorts . In addition, defining a low‐risk group and a high‐risk group based on a cut‐value is conceptually misleading if the prognostic impact is in fact linear: It falsely suggests that there are two qualitatively different subgroups, although in reality, the hazard just varies proportional to the measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the influence of low muscle mass (sarcopenia) and/or poor muscle quality (low radiodensity) on cancer prognosis, reporting prognostic cut‐off values based on the statistical method of optimal stratification for respective parameters. Optimizing a cut‐value by minimizing the P ‐value, however, can lead to bias, namely, an overestimation of the prognostic impact as the cut‐offs so determined heavily dependent on the case mix in the respective study populations, for example, according to age, gender, ethnicity, cancer type, and stage, and consequently cannot be applied uniformly in different cohorts as exemplified by considerable different cut‐off values reported in an Asian cohort compared with North American cohorts . In addition, defining a low‐risk group and a high‐risk group based on a cut‐value is conceptually misleading if the prognostic impact is in fact linear: It falsely suggests that there are two qualitatively different subgroups, although in reality, the hazard just varies proportional to the measurement.…”
Section: Discussionmentioning
confidence: 99%
“…This observation has been confirmed in two large cohort studies of 3241 females with breast cancer and 3262 males and females with colorectal cancer, where low abdominal muscle cross-sectional area was observed in 34-42% of patients, and this was independently associated with a 27-41% higher risk of overall mortality. 35 Another approach is to model the joint effects of muscle and adiposity using phenotype methods. 47 The use of body composition quantified with clinical imaging is, however, not without limitation.…”
Section: Body Mass Indexmentioning
confidence: 99%
“…In patients with acute and chronic illness, depleted skeletal muscle (SM) mass, also referred to as sarcopenia, is a condition associated with underlying disease processes and adverse outcomes . Imaging technologies like dual‐energy x‐ray absorptiometry and computed tomography (CT) are considered gold‐standard references for body composition assessment in research.…”
Section: Introductionmentioning
confidence: 99%